(3OdGFd GdNjQGJ hThGQb GdCfhGQ aj PcQ GdUdGI Ydi GdfHj GdeNJGQs - (3GdLRhdj, eMeO Hf SdjeGf Hf YHO GdQMef, J(B870(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj gOGfG ddEjeGfhHYO gPG aGdZQV aj gPG GdcJGH PcQ GdUdGI Ydi GdfHjhSejJg HcJGH OdGFd GdNjQGJs
(3BNQgG (B:s
(3hUdi Gddg Ydi NjQ Ndbg eMeO hBdg hCUMGHg CLeYjf Edgj EdgfG hGQMefG eYge LejYG HQMeJc jG CQMe GdQGMejfs
(3aj Chdg fbhd hCOYjI HGddZI GdYQHjI hGdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 151s
(3eYLe GdeDdajf(B: 3 / 333s
(3cTa GdXfhf(B: 1 / 759s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs